2008
DOI: 10.1007/s11095-008-9535-1
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Metabolism of Bupropion by Cytochrome P4502B6 (CYP2B6) and Human Liver Microsomes

Abstract: Stereoselective bupropion hydroxylation may have implications for the therapeutic efficacy of bupropion as an antidepressant or smoking cessation therapy, and for the use of bupropion as an in vivo phenotypic probe for CYP2B6 activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
49
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 33 publications
8
49
0
Order By: Relevance
“…Previous studies have shown that CYP2B6 metabolism of bupropion forms hydroxybupropion (Kirchheiner et al, 2003;Coles and Kharasch, 2008;Kharasch et al, 2008;Benowitz et al, 2013;Ilic et al, 2013). In addition, studies have also suggested that other P450s, such as dmd.aspetjournals.org CYP2C19, CYP2E1, and CYP3A4, might have minor roles in the hydroxybupropion formation, but this still needs to be confirmed (Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that CYP2B6 metabolism of bupropion forms hydroxybupropion (Kirchheiner et al, 2003;Coles and Kharasch, 2008;Kharasch et al, 2008;Benowitz et al, 2013;Ilic et al, 2013). In addition, studies have also suggested that other P450s, such as dmd.aspetjournals.org CYP2C19, CYP2E1, and CYP3A4, might have minor roles in the hydroxybupropion formation, but this still needs to be confirmed (Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…This would suggest perhaps the further investigation of the stereoisomers of other racemic CYP2B6 substrates as stereoselectivity could be an important component of this enzyme. A recent study with individual isomers of bupropion [42], (previously identified as a CYP2B6 substrate and now a widely used probe reaction [5,43,44]) indicated stereoselectivity [K m (R) vs (S), 46µM and 34 µM respectively]. When compared to the racemate with a K m of 107.5µM [45].…”
Section: Discussionmentioning
confidence: 99%
“…( R,S )-bupropion undergoes stereoselective oxidative metabolism by cytochrome P450 2B6 (CYP2B6) to form (R,R) - and ( S,S )-hydroxybupropion [2]. Additionally, bupropion is stereoselectively reduced by carbonyl reductase(s) to form erythrohydrobupropion and threohydrobupropion [3].…”
Section: Introductionmentioning
confidence: 99%